Genesis and evolution of a Neoproterozoic magmatic arc: the cordilleran-type granitoids of the Araçuaí Belt, Brazil. - Narduzzi, Francesco (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.